2020
DOI: 10.1016/j.childyouth.2019.104612
|View full text |Cite
|
Sign up to set email alerts
|

The digital divide: Risk and protective factors and the differences in problematic use of digital devices among Hungarian youth

Abstract: A number of psychological factors have been found to be relevant in terms of problematic use of digital devices. Some of them may serve as risk factors, while others mean protection. The main goal of present study was to determine user profiles and to examine differences among them based on several psychological variables using cluster analysis. Data were collected from high school and university students via an online questionnaire from November 2017 to January 2018 (N = 249; females: 62.2%, Mean age = 22.5 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 67 publications
0
19
0
2
Order By: Relevance
“…Considering the negative impact caused by inappropriate use of technologies and electronic devices on adolescents’ quality of life and health, several authors have recently shown interest in examining the risk and protective factors involved in the development and maintenance of such use (e.g., [ 11 , 12 ]). Drawing on the compensatory internet use theory [ 13 ], motivations and their antecedents are considered as important factors for the use of online technology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the negative impact caused by inappropriate use of technologies and electronic devices on adolescents’ quality of life and health, several authors have recently shown interest in examining the risk and protective factors involved in the development and maintenance of such use (e.g., [ 11 , 12 ]). Drawing on the compensatory internet use theory [ 13 ], motivations and their antecedents are considered as important factors for the use of online technology.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, some preliminary findings have found the potential influence of specific dimensions of CSE on problematic technology use. For example, self-esteem [ 52 ] and self-regulation [ 11 ] were significant protective factors against problematic technological use; and neuroticism (as opposite to emotional stability) has been associated to addictive and problematic technology use [ 10 , 53 , 54 , 55 ] among an adolescent population. Therefore, it is expected that adolescents with high CSE will be better able to handle technology use in a responsible and moderate way, even if they have suffered victimization.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that even with problematic smartphone usage, children with good school adaptation may hold protective factors that may buffer its negative impact. In a similar vein, previous studies have demonstrated that protective factors can neutralize or minimize the negative effect of problematic smartphone usage (e.g., Kiss et al, 2020 ). In other words, children with a high level of school adaptation may have access to factors that buffer the adverse effects of problematic smartphone usage.…”
Section: Discussionmentioning
confidence: 82%
“…Results indicated a potential therapeutic role of positivity that decreases internet addiction through its reduction of general distress. Finally, studies have found resilience to be a protective factor of internet addiction in both adults (Hou et al, 2017; Robertson et al, 2018) and adolescents (Kiss et al, 2020; Zhou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%